A Multiscale Perspective on Misfit Dislocations in Oxide Films - Sandiumenge, Felip (Frontiers in Materials, 2019)
Misfit dislocations were conceived by Jan H. van der Merwe in 1949 (Frank, F. C., and van der Merwe, J. H. (1949). One-dimensional dislocations. I and II. Proc. Royal Soc. London. Series A. 198, 205-216 and 216-225), long before they were directly observed by transmission electron microscopy in the early sixties (Matthews, J. W. (1961). The observation of dislocations to accommodate the misfit between crystals with different lattice parameters. Phil. Mag. 6, 1347-1349; Delavignette, P., Tournier, J., and Amelinckx, S. (1961). Direct observation of dislocations due to epitaxy. Phil. Mag. 6, 1419-1420). Since then, their appreciation by the scientific community has evolved from being considered a drawback to being recognized as a challenging opportunity. However, taking full advantage of all their potential, sets out issues that despite being well established in semiconductor or metals, remain poorly understood in transition metal oxides. In this Perspective contribution, we select recent findings on misfit dislocations in La0.7Sr0.3MnO3 under compressive strain, to illustrate effects spanning a range of length scales, like the coupling between strain and defect chemistry in and around their cores, the impact of kinetics on the morphology of dislocated films, or the subtle sensitivity of oxide properties to dislocation strain fields.